Perbaikan Operasional Gudang untuk Mengurangi Komplain Pelanggan menggunakan Six Sigma DMAIC - Erik Sutendi; Riki Ridwan Margana (Widyatama University, 2026)
Company X is a household appliance distributor company facing problems in warehouse operations and inventory control. The high number of customer complaints indicates that the warehouse operational process at Company X has not been running optimally, thus affecting service quality. This study aims to identify complaint categories that are prioritized for improvement, analyze the factors causing complaints, and formulate proposals for warehouse operational improvements to reduce customer complaints. The study uses the Six Sigma method with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. The Define stage is carried out by identifying problems and determining Critical to Quality (CTQ) based on customer complaint data. The Measure stage uses a Pareto Chart, as well as calculations of Defect per Opportunity (DPO), Defect per Million Opportunities (DPMO), and sigma values. The measurement results show a complaint rate of 0.57% of 81,471 transactions with a process capability of 4.1 sigma. The Pareto diagram shows five dominant complaint categories that contribute 84.42% of the total complaints. The Analyze stage uses a Fishbone Diagram to identify the root causes of complaints. The Improve phase proposes the implementation of a barcode-based Warehouse Management System (WMS), SOPs for marketplace product information management, and the 5S method. Furthermore, the Control phase involves implementing Warehouse operational SOPs, monitoring checklists, and periodic audits to continuously monitor the proportion of complaints. The proposed improvements are expected to improve warehouse operational effectiveness and reduce customer complaints.